Has NAFTA Increased Labor Market Integration between the United States and Mexico? - Robertson, Raymond (Published by Oxford University Press on behalf of the World Bank, 2014)
This article analyzes three criteria for labor market integration between Mexico and the United States (U.S.) before and since the North American Free Trade Agreement (NAFTA): the responsiveness of Mexican wages to US wage shocks, the speed at which relative wages return to a long-run differential, and changes in the rate of convergence of absolute wages. Tests for increased integration using these three criteria generate mixed results, which are then explored by directly incorporating trade, foreign direct investment (FDI), and migration. The results suggest that trade and FDI did in fact positively contribute to integration but that the increase in border enforcement depressed Mexican wages, masking the positive benefits.